Y la independencia de Iberoamérica se hizo Varios procesos, múltiples enfoques, una mirada global - Chust, Manuel; Vásquez, Sigfredo (Ariadna Ediciones, 2021)
The definitive crisis of the system in force in Iberian America for 300 years had global consequences, being a phenomenon that was conclusive for the establishment of the hegemony of the West in the 19th and 20th centuries. In And the independence of Ibero-America was made, a set of significant contributions are presented, made from different approaches, but with a comprehensive perspective, which are intended to contribute to a necessary general perception of the study of Latin American independencies. In this way, this book participates in the rich debate in the shadow of the commemorations for the bicentennial, raised with the intention of overcoming local or traditional approaches that, we are sure, will lead to a resignification of the Ibero-American independencies within the interpretation of the creation of Contemporaneity, not only in the Western Hemisphere but in the whole of humanity.